2014
DOI: 10.2147/cpaa.s59376
|View full text |Cite
|
Sign up to set email alerts
|

Differential renal adverse effects of ibuprofen and indomethacin in preterm infants: a review

Abstract: ObjectiveThe objective of this study was to evaluate the extent of renal adverse effects caused by ibuprofen or indomethacin in order to choose the safer drug to administer to preterm infants.MethodsThe following three parameters of renal function were taken into consideration: 1) the urine output; 2) the serum creatinine concentration; and 3) the frequency of oliguria. The bibliographic search was performed using PubMed and Embase databases as search engines.ResultsUrine output ranged from 3.5±1.2 to 4.0±1.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Next to the ongoing discussion on the type of drug being either ibuprofen, indomethacin, or acetaminophen (117)(118)(119)(120)(121)(122)(123)(124), the timing of treatment initiation varies widely between studies, and might explain reported differences in efficacy. As spontaneous ductus closure increases with PNA, part of ductus closure reported in prophylactic and early treatment studies may be due to spontaneous closure rather than drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Next to the ongoing discussion on the type of drug being either ibuprofen, indomethacin, or acetaminophen (117)(118)(119)(120)(121)(122)(123)(124), the timing of treatment initiation varies widely between studies, and might explain reported differences in efficacy. As spontaneous ductus closure increases with PNA, part of ductus closure reported in prophylactic and early treatment studies may be due to spontaneous closure rather than drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the Trial of Indomethacin Prophylaxis in Preterm Infants, the prophylactic administration of indomethacin did not reduce the burden of white matter injury, and the surviving infants exhibited moderate-to-severe cognitive delays at a corrected aged of 18 months [ 202 ]. Additionally, contraindications to indomethacin treatment include nephrotoxicity [ 203 ], adverse cerebral hemodynamics [ 204 ], and an increased risk of serious neonatal complications (e.g., intracranial hemorrhage, necrotizing enterocolitis, and patent ductus arteriosus) [ 202 , 205 ] in preterm infants born before 30 weeks of gestation.…”
Section: Anti-inflammatory Agents In the Treatment Of Inflammation-related Brain Injurymentioning
confidence: 99%
“…By contrast, prophylaxis with indomethacin in extremely low birth weight infants did not improve the rate of survival without neurosensory impairment at 18 months, despite reducing the frequency of severe periventricular and intraventricular hemorrhage (Schmidt et al, 2001). Further, in a large cohort of preterm born infants, NSAIDs during pregnancy was associated with renal side effects (Pacifici, 2014) and an increased risk of quadriparetic and diparetic cerebral palsy (Tyler et al, 2012).…”
Section: Nonsteroidal Anti‐inflammatory Drugsmentioning
confidence: 99%